High-Redshift Galaxies: Light from the Early Universe - Appenzeller, Immo (Springer-Verlag Berlin Heidelberg, 2009)
I The Context -- The Nearby Universe -- The Past and the Future -- II Methods and Tools -- Basic Techniques and their Limitations -- Finding Very Distant Galaxies -- Deriving Physical Parameters -- III Observational Results and their Interpretation -- Observed Properties of High-redshift Galaxies -- The Space Distribution of High-redshift Galaxies -- Interactions with the Intergalactic Medium -- Implications -- IV An Outlook to the Future -- Ongoing Work -- Future Facilities and their Opportunities.
Includes bibliographical references and index
Keywords: Kosmologie; Rotverschiebung; Galaxie